The Situation of Smoke Exposure at Home and Respiratory Problems in Early Childhood, Nakhon Si Thammarat Province - Phetruang, Apinya; Kusol, Kiatkamjorn; Eksirinimit, Thidarat; Jantasuwan, Rachadaporn (Science, Technology, and Social Sciences Procedia, 2023)
This retrospective study aimed to investigate the situation of smoke exposure at home, smoking behaviors among family members, and respiratory problems among young children in Nakhon Si Thammarat Province. Data were collected from primary caregivers over a 6-month period. The sample size was determined using the Krejcie and Morgan sampling method, at a 95 % reliability level, resulting in a sample size of 414 participants. Data collection involved administering a questionnaire to gather information on the personal details of the children and their caregivers, as well as employing a smoke exposure assessment form and a respiratory problem assessment form. The validity of these instruments was confirmed, with a content validity index (CVI) of 1.0 and a Cronbach’s alpha reliability coefficient of 0.8 for the smoke exposure assessment form, and a CVI of 1.0 and a KR-20 reliability coefficient of 0.72 for the respiratory problem assessment form. Descriptive statistics, including percentages, means, and standard deviations (SD), were utilized to analyze the collected data. The results revealed that 51 % of the participants were male, while 49 were female, with an average age of 3.71±0.60 years. The majority of primary caregivers were female (66.2 %), with an average age of 40.28±12.03 years. Regarding smoke exposure at home during early childhood, the study found that fathers (38.9 %) and grandfathers (33.1 %) were the primary caregivers who smoked. The level of smoke exposure was determined to be moderate (52.2 %). Furthermore, it was observed that 68.8 % of children in these households experienced respiratory diseases. The most reported symptoms were nasal congestion, sneezing, and a runny nose (59.7 %), followed by coughing and phlegm production (45.7 %). Additionally, 40.6 % of affected children required hospital or clinic admission. The most prevalent respiratory conditions identified were the common cold (47.6 %), bronchitis (28 %), and allergic rhinitis (19.1 %). Comparison with similar studies conducted in developing countries revealed consistent trends and patterns. Consequently, the development of preventive strategies for respiratory problems in children is crucial, with a particular emphasis on reducing exposure to stimuli such as smoke. Family members should be educated about the importance of refraining from smoking at home to mitigate the severity and occurrence of respiratory problems during early childhood.